Fundamentals of combustion engineering - Mukhopadhyay, Achintya; Sen, Swarnendu (New York, NY : CRC Press, 2019)
This book is an introductory text on fundamental aspects of combustion including thermodynamics, heat and mass transfer and chemical kinetics which are used to systematically derive the basic concepts of combustion. Apart from the fundamental aspects, many of the emerging topics in the field like microscale combustion, combustion dynamics, oxy-fuel combustion and combustion diagnostics are also covered in the book. This would help the beginners in the subject to get initiated to the state of the art topics. Key Features: Coverage of the essential aspects of combustion engineering suitable for both beginners and practicing professionals Topics like entropy generation, microscale combustion, combustion diagnostics, second law-based analysis exclusive to the title Balanced treatment of thermodynamics, transport phenomena and chemical kinetics Discussion on state of the art techniques in combustion diagnostics Illustrates combustion of gaseous, liquid and solid fuels along with emission of pollutants and greenhouse gases
6.4 Determination of Flame Speed6.4.1 Determination of Flame Speed by Bunsen Flame Method; 6.4.2 Determination of Flame Speed by Flat Flame Burner Method; 6.4.3 Determination of Flame Speed by Spherically Propagating Flame Method; 6.5 Simplified Analysis; 6.6 Factors Affecting Flame Speed; 6.6.1 Dependence on Temperature; 6.6.2 Dependence on Pressure; 6.6.3 Dependence on Fuel Type; 6.7 Flame Quenching and Ignition; 6.7.1 Quenching of Ducted Flame Due to Heat Loss; 6.7.2 Minimum Energy for Ignition; 6.8 Flame Propagation in Microscale Combustors
OCLC-licensed vendor bibliographic record.
Keywords: Combustion engineering; TECHNOLOGY & ENGINEERING / Mechanical; SCIENCE / Mechanics / Dynamics / Thermodynamics; TECHNOLOGY / Engineering / Civil; SCIENCE / Energy